Watson: Computer Vision based Software for Summarization of Crime Scenes - Dr. S.V. Kedar, Satvik Sharma, Amit Sarje, Avadhoot Kabadi, Aditya Sathe (Mathematical Statistician and Engineering Applications, 2022)
In today's world, the crime investigation has reached a significant height due to high power and accurate computing technologies of the present time. For any such general investigation, evidences play an important role. Photographs of such scene give the idea of the objects, samples or areas involved in a crime scene. To analyse the digital evidences, various machine learning methods and algorithms are being developed/used. (E.g. blood/weapon/body detection, 3d reconstruction etc.). However, we also need the reports or the shortened summary of such scenes which may need the human intelligence. Inspired by this idea, in this paper, we have introduced our proposed system which generates the summary of a crime scene provided the images of it from different angles. We have also discussed the algorithms, techniques, and limitations of our system.